Impact of the COVID-19 pandemic on vancomycin-resistant Enterococcus bloodstream infections: a 6-year study in Western Greece - Lagadinou, Maria; Michailides, Christos; Chatzigrigoriadis, Christodoulos; Erginousakis, Ioannis; Avramidis, Prodromos; Amerali, Marina; Tasouli, Fotini; Chondroleou, Anna; Skintzi, Katerina; Spiliopoulou, Anastasia; Kolonitsiou, Fevronia; Leonidou, Leonidia; et al. (Frontiers in Microbiology, 2025)
BackgroundAntimicrobial resistance is a critical and growing global health concern. While drug-resistant Gram-negative bacilli pose a significant threat, multidrug-resistant Gram-positive bacteria—such as methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus (VRE), and β-lactamase-resistant Streptococcus pneumoniae—also present serious clinical challenges.AimThis study provides an epidemiological analysis of resistant Gram-positive bacteria, focusing on VRE, at a tertiary university hospital in Western Greece from 2018 to 2023.ResultsA total of 276 blood cultures with vancomycin-resistant Enterococcus spp. were recorded. A significant increase in VRE prevalence was observed in intensive care units (ICUs), with cases rising from 4 in 2020 to 36 in 2021. A broader increase across medical and surgical wards was noted in 2022–2023. Linezolid resistance remained low throughout the study period. Mortality data revealed a marked increase in deaths after 2020 compared to 2018–2019, coinciding with the rise in VRE-related bloodstream infections. The Coronavirus Disease 2019 (COVID-19) pandemic was associated with higher VRE rates in ICU patients, likely due to prolonged hospitalizations, increased use of invasive devices, and broad-spectrum antibiotic use. Resistance rates to both linezolid and tigecycline remained low, while daptomycin resistance showed an increasing trend the same period.ConclusionThe number of VRE increased over the study period. Linezolid and tigecycline remained largely effective, but emerging resistance patterns—particularly to daptomycin—underscore the urgent need for strengthened antimicrobial stewardship and the development of novel therapeutic options to address rising resistance among Gram-positive pathogens.